Editorial - RAMOS HOLGUÍN, BERTHA; Peñaloza Rallón, Anna Carolina (Universidad Pedagógica y Tecnológica de Colombia, 2019)
It is a pleasure for our editorial committee to share with you this new edition of ENLETAWAJOURNAL. This issue highlights the fact that writing is a crucial form of human expression.Thus, this number presents research reports about various themes that range from interculturalityto students' voices to language teaching in indigenous communities. It also explores writing fromthe self-based on authors' lived experiences. The first part of the journal accounts for researchreports as reliable sources about conducted research. The second part includes reflective essaysfrom the students in the 16th M.A. in Language Teaching cohort on topics related to linguisticsand their contexts. The third part of this issue invites readers to enjoy a portrait of the self as ameans of expressing and reflecting about life in a personal way. The works in this volume reflectan opportunity to write with more creativity, insight, and enjoyment. This volume attempts toempower writers “to be better scholars, to live more fully in the world” (Hooks, 1994, p. 6)through the interrogation of homogenized ways of writing.